Model Pertumbuhan Rasional Tanaman Balangeran (Shorea balangeran Korth. Burck) di Lahan Rawa Gambut Kalimantan Tengah : Rational Growth Model of Balangeran Plants (Shorea balangeran Korth. Burck) in Peat Swamp Lands of Central Kalimantan - Wahyudi, Wahyudi; Poerwadi, Petrus; Sudyana, I Nyoman; Rotinsulu, Johanna Maria (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
The balangeran tree (Shorea balangeran Korth. Burck) is a commercial species that grows well in peat swamps. Plant growth can be described through mathematical equations. The research aims to determine the most appropriate harvest time for balangeran plants. The model was then tested for validation, accuracy and coefficient of determination. The results of the research show that the diameter growth model for balangeran plants is namely: y = - 6.94 + 7.26 x / (1+ 0.48 x + (-0.01) x2) with a coefficient of determination of 80%, The equation is valid and quite accurate. Based on this equation, the harvest time for balangeran plants can be determined, namely 29 years, when the average diameter of balangeran plants reaches 30.97 cm.